Predictors of First-Year Medication Adherence in a National Cohort of Veterans Initiating Pre-Exposure Prophylaxis (PrEP) to Prevent HIV Infection. (4th October 2017) - Ohl, Michael; Richardson, Kelly; Beck, Brice; Alexander, Bruce; Van Epps, Puja; Maier, Marissa; Lund, Brian; Vaughan-Sarrazin, Mary
Abstract: Background: Current guidelines for HIV Pre-Exposure Prophylaxis (PrEP) recommend daily use of tenofovir disoproxil fumarate / emtricitabine (TDF/FTC). Little is known about levels and predictors of long-term PrEP medication adherence in routine clinical settings. Methods: We used a previously-validated algorithm and national Veterans Health Administration (VHA) administrative data to identify a cohort of Veterans initiating PrEP during 2012–2015 (i.e., TDF/FTC use, no other antiretroviral use, and no diagnosis codes for HIV, hepatitis B, or needle-stick injury). We used pharmacy refill data to calculate the proportion of days covered (PDC) by TDF/FTC in the 365 days after initiation, and multivariable logistic regression to identify patient characteristics associated with high adherence (i.e., PDC > 0.80). Results: Most (96%) of the 706 Veterans initiating PrEP were men, reflecting the overall demographics of patients in VHA. The median age was 38. Reported race in administrative data was 141 (20.0%) black, 485 (68.7%) white, 42 (5.9%) other, and 38 (5.4%) missing. Only 30 PrEP users (4.2%) lived in rural areas. Co-existing diagnoses included substance use disorder in 264 (37.4%), hypertension in 250 (35.4%), and diabetes in 95 (13.5%). The median PDC for TDF/FTC in the first year was 0.78 (IQR 0.41–0.96), and a minority ( N = 120, 17%) had only a single TDF/FTC fill. Predictors of high adherence were older age (OR 1.88, 95% CI 1.20–2.84 for age 50–64 compared with age < 35); white compared with black race (OR 1.96, 1.30–2.94), Male sex (OR 4.17, 1.67–12.50), absence of a substance use diagnosis (OR 1.47, 1.05–2.04), and presence of diabetes (OR 1.66, 1.02–2.75). Conclusion: Adherence to TDF/FTC in the first year of PrEP was overall high. Racial, gender, and substance-use-related differences in PrEP adherence mirrored those previously described for PrEP uptake. Interventions to promote equitable PrEP uptake should include strategies to support adherence. Disclosures: All authors: No reported disclosures.